Reinserção de abrigados no mercado de trabalho: direito a profissionalização - Silva, Luana Monteiro da (Brasil, 2025)
Social integration of shelter residents is a relevant issue, especially due to the vulnerability these individuals face, often marked by poverty, violence, and lack of family bonds. This study explores the importance of professional training as a fundamental right and a tool for social reintegration, empowering individuals for the job market and promoting financial independence and dignity. A qualitative approach was used, with interviews with shelter residents, social work professionals, and business representatives. Results indicate barriers such as lack of qualifications, stigma, and emotional challenges, highlighting the role of companies and public policies in building a more inclusive society.